Regulation of cardiotrophin-1 expression during mouse embryonic stem cell differentiation by hypoxia and reactive oxygen species - Ateghang, Bernadette; Justus Liebig University Giessen (My University, 2006)
Cardiomyogenesis in differentiating mouse embryonic stem (ES) cells is promoted by cardiotrophin-1 (CT-1), a member of the IL-6 interleukin superfamily and acts through the gp130 cytokine receptor. It was shown that prooxidants (menadione, hydrogen peroxide) as well as chemical (CoCl2) and physiological (1% O2) hypoxia increased CT-1 as well as HIF-1a protein and mRNA expression in embryoid bodies, indicating that CT-1 expression is regulated by reactive oxygen species (ROS) and hypoxia. Treatment with either prooxidants or chemical hypoxia increased gp130phosphorylation and protein expression of NADPH-oxidase subunits p22-phox, p47-phox, p67-phox, as well as Nox-1 and Nox-4 mRNA. Consequently, inhibition of NADPH-oxidase activity by diphenylen iodonium chloride (DPI) and apocynin abolished prooxidant- and chemical hypoxia-induced up-regulation of CT-1 and HIF-1. Prooxidants and chemical hypoxia activated ERK1,2, JNK and p38 as well as PI3-kinase, JAK2 and STAT3. The pro-oxidant and CoCl2-mediated up-regulation of CT-1 and HIF-1 was significantly inhibited in the presence of the ERK1,2 antagonist UO126, the JNK antagonist SP600125, the p38 antagonist SKF86002, the PI3-kinase antagonist LY294002, the JAK-2 antagonist AG490 as well as in the presenceof free radical scavengers. Moreover, developing embryoid bodies derived from HIF-1a-/--ES cells lack cardiomyogenesis, and prooxidants as well as chemical hypoxia failed to upregulate CT-1 expression. Treatment of cells obtained by collagenase dissociation of beating EBs with pro-oxidants and chemical hypoxia resulted in the translocation of CT-1 into the nucleus within 2-4 h. In summary our data demonstrate that CT-1 expression in ES cells is regulated by ROS and HIF-1 and imply a crucial role of CT-1 in survival and proliferation of ES cell-derived cardiac cells. The importance of CT-1 nuclear transport to CT-1 mediated gene expression is still to be determined.

Die Kardiomyogenese in differenzierenden embryonalen Stammzellen der Maus wird durch Cardiotrophin-1 (CT-1) gefördert, einem Mitglied der IL-6 Interleukin Superfamilie, das seine Signale durch den gp130 Rezeptor vermittelt. Es wurde gezeigt, dass sowohl Prooxidantien (Menadione, Wasserstoffperoxid) als auch chemische (CoCl2) und physiologische Hypoxie (1% O2) die CT-1 sowie HIF-1 Protein- und mRNA-Expression in den Embryonalkörperchen erhöhen, was zeigt, dass die CT-1 Expression durch reaktive Sauerstoff- Spezies (ROS) und Hypoxie geregelt wird. Die Behandlung mit Prooxidantien oder mit chemischer Hypoxie erhöhte die gp130 Phosphorylierung und Proteinexpression der NADPH-Oxidase- Untereinheiten p22-phox, p47-phox, p67-phox, sowie die mRNA-Expression von Nox-1 und Nox-4. Dementsprechend führte die Hemmung der NADPH-Oxidase Aktivität durch Diphenylen Iodonium Chloride (DPI) und Apocynin zur Aufhebung der durch Prooxidantien und chemische Hypoxie abhängigen Steigerung der CT-1 und HIF-1 Expression. Prooxidantien und chemische Hypoxie aktivierten ERK1,2, JNKund p38 sowie PI3-kinase, JAK2 und STAT3. Die Menadione- und CoCl2 vermittelte Steigerung von CT-1 and HIF-1 wurde in Anwesenheit des ERK1,2 Antagonisten UO126, des JNK Antagonisten SP600125, des p38 Antagonisten SKF86002, des PI3-Kinase Antagonisten LY294002, des JAK-2 Antagonisten AG490 sowie in Anwesenheit von freien Radikalfängern signifikant gehemmt. Außerdem zeigten die aus HIF-1-/- ES Zellen entwickelten Embryonalkörperchen keine Kardiomyogenese, und die Behandlung mit Prooxidantien sowie chemischer Hypoxie führte nicht zu einer Steigerung der CT-1 Expression. Nach Kollagenaseverdau der schlagenden Areale aus EBs wurden die vereinzelten Zellen mit Menadione und CoCl2 behandelt. Dies führte innerhalb von 2-4 Stunden zum Transport von CT-1 in den Kern.Zusammenfassend zeigen unsere Daten, dass die CT-1 Expression in den ES Zellen von ROS und HIF-1 reguliert wird und deuten eine entscheidende Rolle von CT-1 im Überleben und der Proliferation der ES-abgeleiteten Herzzellen an. Die Bedeutung des CT-1 Kerntransportes für die CT-1-vermittelte Genexpression muss noch festgestellt werden.
Regulierung des cardiotrophin-1 Expression während der Differenzierung von Maus Embryonale Stammzellen durch die Hypoxie und reaktive Sauerstoff-Spezies.
Keywords: ddc:570